Development of Mobile Learning-Based Educational Media to Enhance Understanding of Service Quality in Customer Service - Septia Rizky Widya Lestari; Andi Basuki; Erna Sukmawati (REVIEW OF MULTIDISCIPLINARY EDUCATION, CULTURE AND PEDAGOGY, 2026)
In the modern business landscape, mastering service quality is a crucial competency for vocational graduates entering the workforce. This study aims to develop valid, practical, and effective mobile learning-based educational media to improve students’ understanding of service quality in customer service at SMK Negeri 1 Malang. The research problem focuses on students’ low understanding of the concept of customer service quality as well as the limitations of educational media that support flexible and interactive learning. This study employed the Research and Development (R&D) method using the 4D model, which includes the define, design, develop, and disseminate stages. The research subjects consisted of 10th-grade students in Class MPLB 2 at SMK Negeri 1 Malang. Data collection techniques included an expert validation questionnaire, a user response questionnaire, and pre- and post-tests. The results showed that the developed learning media was categorized as acceptable based on evaluations by subject matter experts and media experts. Furthermore, the media was deemed practical based on the students’ positive responses during the learning process. The effectiveness test results showed an increase in students’ understanding of service quality material, as indicated by N-Gain scores in the moderate to high categories. The findings suggest that mobile learning can serve as an alternative learning medium that supports more flexible, interactive, and contextual vocational learning in customer service courses at vocational high schools.